Permafrost table temperature and active layer thickness variability on James Ross Island, Antarctic Peninsula, in 2004-2021 - Kaplan Pastíriková, Lucia; Hrbáček, Filip; Uxa, Tomáš; Láska, Kamil (The Science of the total environment, 2023)
Climate change and its impacts on sensitive polar ecosystems are relatively little studied in Antarctic regions. Permafrost and active layer changes over time in periglacial regions of the world are important indicators of climate variability. These changes (e. g. permafrost degradation, increasing of the active layer thickness) can have a significant impact on Antarctic terrestrial ecosystems. The study site (AWS-JGM) is located on the Ulu Peninsula in the north of James Ross Island. Ground temperatures at depths of 5, 50, and 75 cm have been measured at the site since 2011, while air temperature began to be measured in 2004. The main objective is to evaluate the year-to-year variability of the reconstructed temperature of the top of the permafrost table and the active layer thickness (ALT) since 2004 based on air temperature data using TTOP and Stefan models, respectively. The models were verified against direct observations from a reference period 2011/12-2020/21 showing a strong correlation of 0.95 (RMSE = 0.52) and 0.84 (RMSE = 3.54) for TTOP and Stefan models, respectively. The reconstructed average temperature of the permafrost table for the period 2004/05-2020/21 was -5.8 °C with a trend of -0.1 °C/decade, while the average air temperature reached -6.6 °C with a trend of 0.6 °C/decade. Air temperatures did not have an increasing trend throughout the period, but in the first part of the period (2004/05-2010/11) showed a decreasing tendency (-1.3 °C/decade). In the period 2011/12-2020/21, it was a warming of 1.9 °C/decade. The average modelled ALT for the period 2004/05-2020/21 reached a value of 60cm with a trend of -1.6 cm/decade. Both models were found to provide reliable results, and thus they significantly expand the information about the permafrost and ALT, which is necessary for a better understanding of their spatiotemporal variability and the impact of climate change on the cryosphere.
Keywords: Active layer; Stefan model; Permafrost; Climate change; Antarctic Peninsula; TTOP model